A Physical Interpretation of the Maximum Likelihood Estimation of a Linear Functional Relationship Model - Hui, Y. V. (Institutional Knowledge at Singapore Management University, 1984)
This paper presents a physical interpretation of estimating the parameters of a linear functional relationship model. The estimates are determined from the stable equilibrium position of a mechanical system. It is found that the estimates obtained from the physical model coincide with the maximum likelihood estimates.